2008
DOI: 10.1016/j.jinorgbio.2007.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Zinc binding ligands and cellular zinc trafficking: Apo-metallothionein, glutathione, TPEN, proteomic zinc, and Zn-Sp1

Abstract: Many cell types contain metal-ion unsaturated metallothionein (MT). Considering the Zn 2+ binding affinity of metallothionein, the existence of this species in the intracellular environment constitutes a substantial "thermodynamic sink." Indeed, the mM concentration of glutathione may be thought of in the same way. In order to understand how apo-MT and the rest of the Zn-proteome manage to co-exist, experiments examined the in vitro reactivity of Zn-proteome with apo-MT, glutathione (GSH), and a series of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 47 publications
8
59
0
Order By: Relevance
“…A previous study had shown that under approximately stoichiometric conditions EDTA reacts with LLC-PK 1 Zn-proteome to extract about 30% of its Zn 2+ [22]. That result was repeated in the present experiment.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…A previous study had shown that under approximately stoichiometric conditions EDTA reacts with LLC-PK 1 Zn-proteome to extract about 30% of its Zn 2+ [22]. That result was repeated in the present experiment.…”
Section: Resultssupporting
confidence: 73%
“…For kinetic or thermodynamic reasons, it is largely unreactive with proteomic Zn 2+ bound to native proteins. It does compete for much of the adventitiously bound Zn 2+ to form Zn(ZQ) 2 and also appears to bind the rest in the form of ternary complexes, which are revealed by a blue-shift in the fluorescence emission spectrum of Zn(ZQ) 2 from 490 nm to 470 nm [19]: normalZnormalnproteomenormalZnormaln+2normalZnormalQnormalZnormalQnormalZnormalnproteomenormalZnormalnnormalZnormalQ Also, as documented in previous studies and below in Figure 5a, 4 μM apometallothionein, which provided 28 μM in Zn 2+ binding sites, removed little if any Zn 2+ from 28 μM Zn-proteome to form Zn-MT [21,22]. Thus, as with ZQ, Zn-proteome is mostly unreactive with an endogenous ligand, apo-MT, that also has a large binding constant for Zn 2+ , 10 11.2 [16].…”
Section: Resultsmentioning
confidence: 80%
“…CA is also known to be a Zn-binding protein, and its activity is dependent on the Zn concentration (38). Additionally, the removal of Zn from Zn-protein complexes extracted from human U87 human glioblastomaastrocytoma cells by TPEN inhibited the function of the transcription factor, Sp1 (39). Although there is currently no information on effects of TPEN on CA activity, we speculate that TPEN may inhibit sperm motility by sequestering Zn away from this enzyme in sperm.…”
Section: Discussionmentioning
confidence: 88%
“…16 A C-terminal TAP-tag under the control of the 35S promoter was cloned without the stop codon into the vector pFGC5941. 26 The plant expression vector was transformed into Agrobacterium tumefaciens strain GV3101. Arabidopsis thaliana was transformed using the floral dip method for A. tumefaciens-mediated gene transfer.…”
Section: Methodsmentioning
confidence: 99%